2015
DOI: 10.1002/pssb.201552430
|View full text |Cite
|
Sign up to set email alerts
|

Domain glasses: Twin planes, Bloch lines, and Bloch points

Abstract: Ferroelastic materials can develop complex domain structures, which have properties of glassy systems (non-ergodicity, glass dynamics, glass transitions, and freezing). Four characteristic temperatures are defined for such domain glasses: the dynamical nucleation temperature T d where local correlated clusters can form glass states within a (tweed-) nano structure, T o the Vogel-Fulcher temperature of these precursor nanostructures, T pt the phase transition temperature where the (ferroelastic) transition occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 100 publications
3
17
0
Order By: Relevance
“…And this year Salje et al [12][13][14] found that ferroelastics are described well by hydrodynamics. The modest breakthrough in the present case follows the recent paper by Scott,3 which suggests that if indeed domain walls follow hydrodynamic flow, they should exhibit hydrodynamic instabilities also.…”
Section: P2mentioning
confidence: 98%
See 1 more Smart Citation
“…And this year Salje et al [12][13][14] found that ferroelastics are described well by hydrodynamics. The modest breakthrough in the present case follows the recent paper by Scott,3 which suggests that if indeed domain walls follow hydrodynamic flow, they should exhibit hydrodynamic instabilities also.…”
Section: P2mentioning
confidence: 98%
“…5,[12][13][14][15] Salje's Model: The basic assumption in Salje's model is that unlike ferroelectric switching, the hysteresis in ferroelastic switching is dominated by continuum fluid mechanics and not the lattice symmetry. He points out that for the strain reversal step from -S to +S, under a positive (reversing) stress to an initially negative strain, the ferroelastic hysteresis is dominated by viscous flow, with a complex domain structure sometimes p.6 describable as a "domain glass.…”
Section: Helfrich-hurault Mechanismmentioning
confidence: 99%
“…Very recently, Salje et al 18,19 proposed the existence of glasses in ferroelastic systems, appearing without the need for any defects, which led him to the concept of "domain glass". The basic idea 20 is that the domain boundaries can generate the defects intrinsically and, at a certain density of domain walls, jamming leads to a Vogel-Fulcher type slowing down of the dynamics around T VF .…”
Section: Introductionmentioning
confidence: 99%
“…Tweed has another property: it can form a domain glass with a nonergodic response to external forcing. Domain glass [29,30] can contain polar nanoregions, which are known to exist in relaxor materials [31][32][33][34]. Complex domain structures, including tweed, may be stabilized by defects, while dynamic tweed [26] exists also for very low defect concentrations [35].…”
Section: Introductionmentioning
confidence: 99%